Investigating the use of Sepedi and English to initiate students into the discourse of a discipline in a first year university course. - Yafele, Simbayi (My University, 2009)
This research project set out to investigate the use of an African language, in this case, Sepedi as an academic language of teaching and learning of first year students in the academic subject of Communication Theory at tertiary education level. Of interest was how effective Sepedi is as an academic language of learning and instruction. The focus was on investigating to what extent using a mother-tongue in academia opens up learning possibilities for learners. The research intended to explore whether it is reasonable and practicable to use an African language (in this case Sepedi) in the teaching and learning of Communication Theory in a first year diploma level Communication Skills class. Of interest therefore was whether Sepedi is useful and is a viable academic language in the pedagogy of Communication Theory in a higher education Communication Skills course. The methods used in the research were qualitative and took the form of a teaching intervention in which a class of Sepedi speaking students voluntarily participated in two lessons in which Sepedi and English were used respectively as a medium of instruction for Communication Theory. Both lessons were observed by the researcher. The class observations were video-recorded and audio-recorded then transcribed for discourse and thematic analysis of the learning and teaching experiences of the participants. Methods used also included a focus group interview and individual interviews and artifacts in the form of an evaluated written formative task and reflective pieces. This was important for evaluating the extent of learning from the lessons observed. Participants’ language biographies were also compiled for purposes of writing up each student’s profile. The purpose of using all these instruments was to use data from one instrument to positively inform the next and for information to be finally triangulated. The research findings suggest that the use of Sepedi (African languages) in the classroom could play a significant role in scaffolding and mediating students who are struggling at first year level in universities. A mixture of African languages and English involving code-switching and mixing may have pedagogical advantages. Also, the iv findings suggest that institutions need to support African languages as languages of accessing academic discourse. However use of English as a Language of Learning and Teaching (LOLT) is still necessary and as such English remains dominant and indispensable in academia.